Character Education for Children in Islamic Boarding Schools: Psychological Perspective - Siti Mumun Muniroh (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
Islamic boarding school has been questioned about its urgency in building and educating the character of the nation's generation along with social dynamics, the development of science and technology. Not to mention, Islamic boarding school (pesantren) is notorious for the bad image as the center of fundamentalism, radicalism, and terrorism. This study analyses the roles and strategies used by Islamic boarding schools in shaping the character of children. This research is a qualitative research using interviews, observations and documentation to obtain the data. It was conducted on children at Salafiyah Syafi'iyah Islamic Boarding School, Pekalongan Regency. The results of the study indicated that the character education taught in Islamic boarding schools starts from the cognitive aspect which are; teach morality, knowledge of good and bad, from waking up to going back to sleep. Through a child psychology approach, the students are invited to practice moral values into daily characters, which are carried out in stages by giving them act to follow, performed by the kiyai (grand teachers), caretakers, and teachers. The results of this study showed that habituation as a behavioral and humanistic action is the key to the success of islamic boarding school in shaping and educating children's character to be kind and care about others and their surrounding. A boarding school is an important instrument in maintaining and creating positive and progressive characters for children.